Tumor-specific frequencies and ocular melanoma. (3rd April 2017) - Milham, Samuel; Stetzer, David
ABSTRACT: Specific kilohertz frequencies in the environment from variable frequency drives on electric motors at a liquid natural gas compressor and storage station on a natural gas pipeline seem to be associated with the development of a very rare cancer, ocular melanoma, at a high school and in individuals living or working in a neighborhood near the plant. Primary neutral-to-earth oscilloscope voltage waveforms and spectra measured near the high school were nearly identical to the ground voltage 2.3 miles away at the gas pipeline. Peak frequencies of 7440 and 19, 980 Hz were found at both places. The electric utility practice of using the earth as a conduit for return currents facilitated this exposure.